Role of the mentor's comments in the performance of mathematics teachers (2015)
We study the relationship between mentorsâ ¿ and mathematics teachersâ ¿ performance in an education program. To this end, we characterize the relationship between the changes made in the written productions of three groups of teachers and the characteristics of their mentorsâ ¿ comments that could motivate those changesâ ¿type of comment, content, and knowledge type. The analysis of these relationships was performed with the help of contingency tables and logistic regressions. We found that, for the whole group of teachers, the changes made by them depend on the type of knowledge and on the content to which the comments refer.